UPI community services actions to combat stunting in Ciherang Village, Cianjur - Fauziah Fauziah; Ilham Firdaus; Santi Sukmawati (Universitas Pendidikan Indonesia, 2024)
Stunting is a significant nutritional problem and is currently prevalent in Indonesia. The problem of stunting will have a negative impact on the physical growth and brain development of children so that it can affect the quality of human resources, worsen intergenerational poverty, and have a negative impact on the country's economic growth, so this problem must be prevented and addressed immediately. This community service aims to increase public awareness and education about preventing stunting through Kuliah Kerja Nyata (KKN) program in Ciherang Village, Cianjur. The community service carried out by KKN-T students from the Indonesian Education University, through seminars and talk shows with the theme